Benefits of Dance Therapy in Overweight and Obese Women - Katia Rodríguez Palacios; Isaac Rodríguez Palacios; Lázaro Dionisio Rojas Matsuda; Yarisel López Pérez; Ismaray Sacerio González; Ivis Triana Oquendo (Revista Finlay, 2021)
Background: therapeutic physical culture programs accompanied by adequate nutritional advice in groups of obese people, is a common practice to reduce excess weight in people. Objective: to evaluate the benefits of the dance therapy program in its Zumba modality combined with Tae Bo, in overweight and obese women between 20 and 60 years old, in an area of the Pueblo Griffo Cienfuegos municipality. Method: a community intervention study of the before and after type was carried out, 47 women from a universe of 56 were studied, anthropometric variables were measured at the beginning, at one month and at two months of the exercise program. The results are presented in tables and graphs and statistical inference tests (difference between means) were applied to determine the differences between each stage with a requirement of 95 %. Results: the values of the body mass index, weight in Kg, skin folds and the measurements of the abdomen and waist diameter decreased, which reflects the weight loss and body fat. In addition, there was a decrease in heart rate and in the results of the Ruffier-Dickson functional test, which indicates an improvement in the functions of the cardiovascular system. All the results were highly significant. Conclusions: these results show that the therapeutic program developed in Cienfuegos with nutritional advice, is effective to reduce weight and body fat and also to improve the functioning of the cardiovascular system.